Metaomics unveils the contribution of Alteromonas bacteria to carbon cycling in marine oxygen minimum zones - Henríquez-Castillo, Carlos; Plominsky, Alvaro M.; Ramírez-Flandes, Salvador; Bertagnolli, Anthony D.; Stewart, Frank J.; Ulloa, Osvaldo (Frontiers in Marine Science, 2022)
Gammaproteobacteria of the genus Alteromonas are prominent members of the pelagic marine microbial communities, playing critical roles in the aerobic degradation of particulate organic matter. Comparative genomic studies of these organisms have mainly focused on the metabolic and genomic plasticity of strains isolated primarily from oxygenated environments. In this study, we show that Alteromonas significantly contribute to microbial communities from suboxic waters in both the free-living (FL) and particle-attached (PA) fractions, but with a considerable decrease in abundance in the anoxic waters. The highest proportion of Alteromonas transcripts was found within the secondary fluorescence maximum (SFM) in OMZs. This metatranscriptomic information suggests an in situ coupling of Alteromonas iron (Fe) and carbon metabolisms and a relevant role in the glyoxylate cycle. This study demonstrates that Alteromonas is an abundant and active member of OMZ-associated microbial communities, with a potentially significant impact on the carbon cycling in these ecosystems. These results provide valuable environmental evidence to support previous culture-based studies assessing the physiology and ecology of these ubiquitous marine heterotrophs under low-oxygen conditions.